PERUBAHAN KOMPONEN KIMIA BUAH MAKADAMIA (MACADAMIA HILDEBRANDII STEEN) SELAMA PENYIMPANAN - Abdul Hakim Lukman; Toga Silitonga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
This work investigates the use of macadamia (Macadamia hildebrandii Steen) fruit. The samples were obtained from Forest District of Simalungun, North Sumatera province of Indonesia. The nut samples were allowed to stand for a period of zero week as control, the others were kept for 4 and 8 weeks. The macadamia kernels were also stored for 4 and 8 weeks. The analyses comprised of the determination of moisture. ash, fat and protein contents.The study reveals that the moisture content varies from 17. 7 - 24.6 percent, ash from 2. 7 - 2.9 percent, fat from0.9 - 2.0 percent, and protein from 6.3 - 8.4 percent. Themoisture, fat, and protein contents were effected by fruit condition and storage time, while ash contents not influenced. The macadamia kernels stored for 8 weeks have smaller moisture content. Fat content of macadamia nuts decreased at stored for 4 and 8 weeks,and protein content of macada-mia nuts and kernels decreased at stored for